When things get hot: Thermoregulation behavior in the lizard Sceloporus aeneus at different thermal conditions. (April 2020) - Rangel-Patiño, Carlos Alejandro; Mastachi-Loza, Carlos Alberto; Eifler, Douglas; García-Morales, Carla; Ruiz-Gómez, María de Lourdes
Abstract: Rising environmental temperatures have become a global threat for ectotherms, with the increasing risk of overheating promoting population declines. Flexible thermoregulatory behavior might be a plausible mechanism to mitigate the effects of extreme temperatures. We experimentally evaluated thermoregulatory behavior in the bunchgrass lizard, Sceloporus aeneus, at three different environmental temperatures (25, 35 and 45 °C) both with and without a thermal refuge. We recorded themoregulatory behaviors (body posture and movement between hot and cold patches) and compared individual lizards across all experimental temperature and shelter combinations. Behavioral thermoregulation in S. aeneus was characterized by the expression of five body postures, whose frequencies varied based on environmental temperature and microthermal conditions. Behavioral responses allowed lizards to maintain a mean body temperature <40 °C, the critical thermal maximum for temperate species, even at extreme environmental temperatures (45 °C). Although S. aeneus express an array of behavioral postures that provide an effective mechanism to cope with elevating temperatures, the presence of a thermal refuge was important to better achieve this. Together, our study offers a novel method to evaluate microhabitat preference that encompasses both behavioral observations and time-space analysis based on the ambient thermal distribution, a consideration that can aid in the formulation of more accurate predictions on ectotherm vulnerability related to increasing global environmental temperatures. Highlights: Sceloporus aeneus presents a flexible thermoregulation behavior. Efficient thermorregulation is attained with body postures and habitat selection. Thermoregulation behavior can prevent reaching high critical body temperatures. An heterogeneous microhabitat is important for ectotherm's thermoregulation.